Displacement Induced Joblessness - Ruhm, Christopher J. (The Review of Economics and Statistics, 1991)
Previous research examining the nonemployment of displaced workers suffers from methodological flaws which reinforce widely held but substantially incorrect views about the pattern of postseparation joblessness. In particular, adjustment difficulties have been overstated for nonwhites, long tenure workers, and those terminated during periods of high unemployment and underestimated for persons in manufacturing industries or white collar occupations.